2011
DOI: 10.1002/esp.2218
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling driving factors for large rock–ice avalanche mobility

Abstract: Large rock-ice avalanches have attracted attention from scientists for decades and some of these events have caused high numbers of fatalities. A relation between rock slope instabilities in cold high mountain areas and climate change is currently becoming more evident and questions about possible consequences and hazard scenarios in densely populated high mountain regions leading beyond historical precedence are rising. To improve hazard assessment of potential rock-ice avalanches, their mobility is a critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
126
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(134 citation statements)
references
References 122 publications
(194 reference statements)
5
126
0
3
Order By: Relevance
“…Ice-rock avalanches were similarly simulated with high ξ parameters, but much lower µ values, consistent for DAN3D and RAMMS. This parameter space may reflect lower friction of the ice and the presence of porewater due to melting of the ice (Schneider et al, 2011). The parameter space shown for snow avalanches are suggested values (Bartelt et al, 2013a), based on experience of back-calculated observed snow avalanches.…”
Section: Ramms-df Dan3dmentioning
confidence: 99%
“…Ice-rock avalanches were similarly simulated with high ξ parameters, but much lower µ values, consistent for DAN3D and RAMMS. This parameter space may reflect lower friction of the ice and the presence of porewater due to melting of the ice (Schneider et al, 2011). The parameter space shown for snow avalanches are suggested values (Bartelt et al, 2013a), based on experience of back-calculated observed snow avalanches.…”
Section: Ramms-df Dan3dmentioning
confidence: 99%
“…This can be further extended due to the influence of ice contained in the moving mass or the trajectory running over glacier ice (Schneider et al, 2011). Furthermore, landslides in mountain environments are typically complex, i.e.…”
Section: Persistence and Impacts Of Permafrost Thaw In The Hkhmentioning
confidence: 99%
“…Furthermore, climate change is exacerbating glacial retreat and mass loss, making a major avalanche event more likely (Schneider et al, 2011). In the Mount Everest region alone (Figure 1), glacier-wide mass loss averages around 0.52 m w.e.…”
Section: Introductionmentioning
confidence: 99%